ANALISIS YURIDIS BERLAKUNYA PP NO. 11 TAHUN 2010 TENTANG PENERTIBAN DAN PENDAYAGUNAAN TANAH TERLANTAR DAN PERMASALAHAN YANG DITIMBULKAN - BAMBANG DIPA SARAGIH (PREMISE LAW JURNAL, 2015)
The Objective of the research was to analyze the control and the efficient use of fallow (uncultivated) land, according to the prevailing legal system, either the law which specifically regulates the control and the efficient use of fallow land or the law which is indirectly related to fallow land The research was judicial normative which used legal and conceptual approach.The result of the research showed that the authority to control fallow land was the delegation of authority in which the President delegated his authority to the Head of the National Land Board of the Republic of Indonesia to control fallow land, according to Article 17 of PP No. 11/2010. In the implementation of the control, Committee C that had the authority to identify and to study land which is indicated as fallow was established. The mechanism of controlling fallow land was through some stages: inventorying land which was allegedly fallow, identifying and studying land which was allegedly fallow, giving warning to people entitled to the land, confirming fallow land, fallow land was used to people’s interest through agrarian reform, State’s strategic program, and State’s general reserves had to be in line with Regional Layout Program. Keywords : Control, Efficient Use, Fallow Land, Land Use